The effect of thread depth on the fatigue strength of AISI 4140 bolt material as a retainer and fastener for a screw conveyor - M Dalil (BKS-TM Indonesia, 2025)
The bolts used to retainer and fasten the shaft of the screw conveyor, which functions to transport wood chips to the cooking process in paper manufacturing, have experienced failure. The failure occurred in the form of a perpendicular fracture on the threaded section of the bolt. This damage significantly disrupts wood processing operations, making it important to investigate the causes. The causes of bolt fracture and its short service life were analyzed by studying the effect of thread pitch variations of 2.5 mm and 2 mm. The materials tested were Valmet (VME) and Valmet (VMC), which are equivalent to AISI 4140. The fatigue test was conducted using a cantilever rotating bending method with the test specimens according to ASTM E466M standards. The results showed that to achieve infinite life, the stress level must be below 95 MPa. Thread pitch has a significant effect: VME bolts with a thread pitch of 2 mm showed a 17% longer endurance than bolts pitch of 2.5 mm, while VMC bolts with a thread pitch of 2 mm had a 15% longer endurance than bolts pitch of 2.5 mm. Furthermore, VME bolts showed 11% higher fatigue endurance than VMC bolts. The endurance of VMC bolts decreases due to the presence of more cracks and voids in the VMC material. This defect is related to the lower chromium (Cr) content in VMC. cracks and voids is exacerbated by the heat treatment, which reduces the effectiveness of alloying elements in delaying crack formation on the surface.